Endovascular Stenting for Chronic Headache Secondary to Cerebral Venous Sinus Stenosis: A Case Report - Izza Ayudia Hakim; Bagus Dermawan; Yingying Zhang; Guangzheng Zhang (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: CVSS is an underdiagnosed but reversible cause of chronic headache Venous stenting effectively restores venous outflow and reduces ICP Early recognition and intervention lead to rapid and sustained symptoms resolution ABSTRACT Introduction: Chronic headache poses a significant diagnostic and therapeutic challenge. Cerebral venous sinus stenosis (CVSS) is an underrecognized yet important etiology in which stenosis impairs venous outflow and elevates intracranial pressure, leading to headache. Endovascular stenting offers a therapeutic approach by mechanically restoring venous flow. Case: A 43-year-old female presented with a chronic headache for 3 months, refractory to multimodal medical therapy. Digital subtraction angiography (DSA) confirmed stenosis in the bilateral transverse sinuses. The patient subsequently underwent successful endovascular venous stenting. Conclusion: This case underscores that CVSS is a potentially treatable cause of chronic headache. Endovascular intervention can provide rapid symptomatic relief for patients with medically refractory headache secondary to venous sinus stenosis. Long-term follow-up remains essential to confirm sustained benefit.